Examining Career Opportunities for Unemployed Graduate Teachers in Zambia: A Case of Lusaka Urban District - Kashumba Kabombo; Chanda Chansa Thelma; Loveness Ngulube (Archives of Current Research International, 2025)
This study employed a sequential explanatory mixed-methods design to investigate career opportunities for unemployed graduate teachers in Lusaka District, Zambia. Graduate teacher unemployment has become a pressing socioeconomic and policy concern, resulting from both supply-side factors such as the overproduction of graduates and demand-side constraints including limited recruitment. Quantitative data were collected from 400 unemployed graduate teachers using structured surveys and analyzed in SPSS, while qualitative insights were gathered through in-depth interviews with 20 purposively selected participants. Logistic regression analysis revealed that limited government recruitment (OR = 0.43, p = .001), insufficient teaching experience (OR = 0.59, p = .013), and favoritism in hiring (OR = 0.67, p = .045) significantly reduced employment odds. Chi-square tests indicated significant differences in employment outcomes across training institutions (p = .02). Thematic analysis of qualitative data highlighted a persistent cycle where lack of experience hindered employment opportunities, yet such experience could only be obtained through unstable, short-term teaching roles. The study recommends that the government increase recruitment funding and establish structured internship and induction programs to bridge the gap between training and employment. Furthermore, universities should revise curricula to reflect classroom realities and introduce extended practicum placements in diverse educational settings. This research contributes to the existing literature by providing empirical evidence on the specific structural and institutional barriers affecting graduate teachers in Zambia. The findings hold relevance for education policymakers, higher education institutions, and labor market stakeholders seeking to design targeted interventions that improve graduate employability and address teacher unemployment at both systemic and programmatic levels.